Application of Performance Management in the Jogja Archive Diorama - Lestari, Nur Puji; Roihaanah, Rifdah; Abdul Azus, Lal (Jurnal Toursci, 2024)
This research is a Case Study on Display. The Jogja Archive Diorama was established on February 24, 2022. In the Jogja Archives Diorama, various archive collections are presented that tell the story from the beginning of the Kingdom of Mataram to the Privileges of Yogyakarta. The goal to be achieved is to find out how the Jogja Archive Diorama Display. The research method used is qualitative, with a theoretical approach regarding the display. Descriptive research is research intended to investigate the circumstances, conditions, or other things mentioned, and the results are presented in the form of research reports based on data by presenting, analyzing, and interpreting them. The data collection method used is interviews, observations, and documentation at the Jogja Archive Diorama. The results obtained in this study are Storyline and how to present archives with different nuances. Adjustments were also made to several aspects of the display by the Jogja Archives Diorama using the theory from the book Weighing the Space of Styling by Mikke Susanto. This study concludes That 250 artists and technologists, audio-video practitioners, readiness experts, historians, academics, and practitioners from various fields of science help supervise the study. Some exhibition materials or information are sourced from DPAD DIY, domestic and foreign institutions, and private collections.